How much are the incidental abnormalities on brain MRI clinically significant in otolaryngology practice? - Kalaycık Ertugay, Çiğdem; Özbal Koç, Ayça; Çevik, Halime; Erbek, Sermed (ENT Updates, 2016)
Objective: We aimed to investigate the frequency of incidental diagnosis of paranasal sinus and mastoid abnormalities on brain magnetic resonance imaging (MRI) and its correlation with symptoms of patients. Methods: We examined 100 patients who underwent brain MRI due to several different complaints other than sinusitis and mastoiditis. The patients who had any nasal or otologic pathology in otolaryngology examination were excluded from the study. Afterwards, a total of 65 patients were included into the study. The questionnaire consisted of otological symptoms and Sino-nasal Outcome Test (SNOT-20), Lund and Mackay scoring system for rhinosinusitis were filled by all patients immediately prior to imaging. The analysis of the MRI scan in terms of rhinosinusitis according to the Lund-Mackay radiological scoring and mastoiditis was performed by the same radiologist. Results: The mean age of 65 patients was 46.62±17.73 years. Eighteen (27.7%) of these were men and 47 (72.3%) were women. In 26 (40%) of 65 patients, MRI demonstrated mastoiditis. We could not find any statistically significant correlation between mastoiditis and upper respiratory tract infection (p=0.896). There was no statistically significant relationship between radiological scores and total sinus symptom scores (p=0.93). Additionally, we could not find any correlation between radiological scores and SNOT-20 (p=0.923). Conclusion: Our findings demonstrated that although some of these patients had various symptoms of sinus or mastoid diseases, these symptoms had no statistically significant correlation with the radiological diagnosis. In conclusion, radiologists should advise clinical correlation of their radiologic findings rather than reporting a clinical diagnosis such as sinusitis and mastoiditis.